A Functional Approach to Java Augmenting Object-Oriented Java Code with Functional Principles - Weidig, Ben (O’Reilly Media, Inc, 2024)
ava developers usually tackle the complexity of software development through object-oriented programming (OOP). But not every problem is a good match for OOP. The functional programming (FP) paradigm offers you another approach to solving problems, and Java provides easy-to-grasp FP tools such as lambda expressions and Streams. If you're interested in applying FP concepts to your Java code, this book is for you.